Dynamics of Stroke Incidence and Mortality Indicators over Eight-Year Period in the Territories Included into the Federal Program of Reorganization of Care for Patients with Stroke - O. A. Klochikhina (Acta Biomedica Scientifica, 2021)
Background. Stroke is a severe medical, social and economic burden for all countries of the world. The leading indicators characterizing the “epidemiological picture” of stroke are the incidence and mortality rates from stroke.Aims. Analyze the dynamics of stroke incidence and mortality rates in the regions of Russia that were included in the federal program for reorganizing care for patients with stroke for the period from 2009 to 2016.Material and methods. The study was based on the data of the territorial-population register for seven study areas in the regions of Russia that were included in the federal program for reorganizing care for patients with stroke (Republic of Bashkortostan, Sverdlovsk region, Republic of Tatarstan, Sakhalin region, Stavropol Territory, Ivanovo Region and Irkutsk Region). The age of the examined persons was 25 years and older.Results. In the period from 2009 to 2016, in the studied territories, there was a consistent stable decrease in the value of the stroke incidence rate. Stroke mortality rates fluctuated with a single increase in 2012. When comparing the average incidence of stroke and mortality from it between 2009 and 2016, we discovered a statistically significant decrease in the incidence of stroke – by 1.4 times and in the rate of mortality from stroke – by 2.3 times. According to the results of the cluster analysis, we revealed a significant conformity (similarity) of mortality rates between regions by 2016 and the absence of monotony (stability) of the rate of stroke incidence.Conclusion. In all the regions under study, an almost systematic annual decrease in the incidence and mortality rates from stroke among the adult population was revealed in seven studied territories. The results of cluster analysis of the “picture” of stroke incidence and mortality from it also demonstrate a positive trend by 2016 in all studied territories. Only one of the studied territories – the Republic of Tatarstan – despite the presence of a positive dynamics of stroke incidence over an eight-year period, in 2016 belonged to the rank with a high integral incidence rate.